2003
DOI: 10.1002/art.11289
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular nucleotide metabolism and signaling in the pathophysiology of articular cartilage

Abstract: Characteristic mass differences between fragment ions from backbone cleavage of RNA by electron detachment (d, w) and fragment ions from collisionally activated dissociation (c, y) provide extensive sequence information (see picture). Structure analysis by this approach should be especially useful for the detailed characterization of synthetic or post‐transcriptionally modified RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 174 publications
(176 reference statements)
0
13
0
Order By: Relevance
“…The chondrocytes, the unique cell type residing in cartilage [54,55], can release PGE 2 [56], a major contributor of inflammatory pain in arthritis conditions, that subsequently acts through a variety of prostanoids receptors expressed in peripheral sensory neurons and spinal cord [57]. A previous in vitro study showed that ATP and α,β-meATP (P2X3 agonist, [14] increase PGE 2 production, an effect that was blocked by the selective P2X3 and P2X2/3 receptors antagonist A317491, indicating a role of P2X3 receptors in PGE 2 release by chondrocytes [18].…”
Section: Discussionmentioning
confidence: 99%
“…The chondrocytes, the unique cell type residing in cartilage [54,55], can release PGE 2 [56], a major contributor of inflammatory pain in arthritis conditions, that subsequently acts through a variety of prostanoids receptors expressed in peripheral sensory neurons and spinal cord [57]. A previous in vitro study showed that ATP and α,β-meATP (P2X3 agonist, [14] increase PGE 2 production, an effect that was blocked by the selective P2X3 and P2X2/3 receptors antagonist A317491, indicating a role of P2X3 receptors in PGE 2 release by chondrocytes [18].…”
Section: Discussionmentioning
confidence: 99%
“…Once released from the cell, ATP may activate P2 receptors triggering intracellular Ca 2+ signalling cascades. Indeed, the activation of P2 receptors following mechanically induced ATP release or addition of endogenous ATP has been shown to have an anabolic effect, with an upregulation in proteoglycan and collagen synthesis and cell proliferation (Kaplan et al 1996;Brown et al 1997;Croucher et al 2000;Picher et al 2003;Millward-Sadler et al 2004;Chowdhury & Knight, 2006). Furthermore, there is a corresponding down-regulation in MMP expression and nitric oxide release.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have implicated a similar autoregulatory pathway in differentiating cells of chicken chondrogenic cell cultures, with P2X4 ionotropic purinergic receptor being the most likely candidate [10,11]. Given that CPCs were originally derived from OA-affected articular cartilage wherein extracellular nucleotides released along with inflammatory mediators may be considered as important ligands of purinergic receptors [41], we aimed to study whether CPCs were able to respond to nucleotide stimulation by P1 and/or P2 receptor activation.…”
Section: Purinergic Signalling In Cpcs and Autocrine/paracrine Regulamentioning
confidence: 99%